Immunological changes induced by ovaprim in the freshwater catfish, Heteropneustes fossilis (Bloch) - Dash, Kalpana; Singh, B N; Pandey, A K; Ayyappan, S (Indian Journal of Fisheries, 2011)
Haemagglutination assay (HA), humoral-mediated specific immune response and alternative pathway of complement-mediated haemolysis (APCH50) were performed to evaluate the immunological responses of the synthetic hormone drug ovaprim in Heteropneustes fossilis. It was found that ovaprim suppresses the haemagglutinin as well as the specific antibody titres of the catfish sera against rabbit erythrocytes (RaRBCs) and bovine serum albumin (BSA) antigen while combination with |3-glucan restored its normal activity indicating its immunomodulatory effect. Furthermore, APCH50 unit of fish sera was remarkably decreased by ovaprim treatment. Anti-ovaprim antibody could not be detected in serum of the treated catfish.